SISTEM PAKAR DETEKSI KERUSAKAN HARDWARE HANDPHONE BERBASIS DESKTOP - Eka Lilla Ananta; Lie Jasa; Putu Arya Mertasana (Jurnal SPEKTRUM, 2018)
Expert System to Detection Damage of Handphone Hardware Based Desktop Based is an application used to obtain a solution in overcoming damage to mobile phones. During this time people have difficulty when faced with obstacles and damage that occurred on their mobile phone. Interaction model between system and user using question and answer model, and have knowledge base system for Knowledge Engineer in order to add new knowledge. This system used backward chainning method. Tree diagram that are modeled on the rules of the knowledge base are stored in the MySQL database and in the making of the system using the Visual Basic 6.0 programming language. The use of backward chainning method can help the user to get mobile damage solution, the solution has been obtained can give the user a knowledge of damage to his mobile phone.